67.1k views
5 votes
6(7b + 4) = -60
What is the solution to the equation??

2 Answers

3 votes

Answer:

b= -2

Explanation:

User IronFlare
by
4.8k points
3 votes

Answer:

B = -2

Explanation:

Simplifying

6(7b + 4) = -60

Reorder the terms:

6(4 + 7b) = -60

(4 * 6 + 7b * 6) = -60

(24 + 42b) = -60

Solving

24 + 42b = -60

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-24' to each side of the equation.

24 + -24 + 42b = -60 + -24

Combine like terms: 24 + -24 = 0

0 + 42b = -60 + -24

42b = -60 + -24

Combine like terms: -60 + -24 = -84

42b = -84

Divide each side by '42'.

b = -2

Simplifying

b = -2

User Thibault
by
4.9k points